Post-Ottoman Coexistence - Bryant, Rebecca (Berghahn Books, 2016)
In Southeast Europe, the Balkans, and Middle East, scholars often refer to the "peaceful coexistence" of various religious and ethnic groups under the Ottoman Empire before ethnonationalist conflicts dissolved that shared space and created legacies of division. "Post-Ottoman Coexistence", interrogates ways of living together and asks what practices enabled centuries of cooperation and sharing, as well as how and when such sharing was disrupted. Contributors discuss both historical and contemporary practices of coexistence within the context of ethno-national conflict and its aftermath.